Pola Komunikasi Orang Tua Dan Anak Remaja Di Masa Modernisasi Pada Kelurahan Jaticempaka Pondok Gede - Wear, Tursina Arafat; Syarah, Maya May; Santoso, Ade Budi (Prisani Cendekia Institute, 2023)
Abstract: The process of providing information and conveying understanding between two or more people is known as interpersonal communication. The purpose of this study is to characterize the interpersona l communication that takes place between parents and kids in the present period. This kind of study is a qualitative descriptive study that explains how parents and kids interact with one another. The community, particularly the parents who reside in Jati Cempaka Pondok Gede Village, are the subjects of this study. This method of gathering data includes observation, interviewing, and documentation. Data reduction, data presentation , conclusion drawing, and Miles and Huberman's interactive data analysis technique were the approaches used for data processing and analysis. The findings of this study demonstrate that parents and kids in the Jati Cempaka Pondok Gede sub-district region engage in interpersonal contact by being honest about contemporary issues, particularly the impact of technology and the internet. Parents continue to watch over, encourage, and respect their children's privacy, though. The development of trust between parents and children depends on this.